2005
DOI: 10.1007/s10528-005-1505-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of Canine Pre-B-Cell Colony-Enhancing Factor

Abstract: During our previous attempt to search for the candidate genes to acute lung injury (ALI), we unexpectedly identified PBEF as the most highly upregulated gene in a canine model of ALI by crosshybridizing canine lung cRNA to the Affymetrix human gene chip HG-U133A. The result suggested that PBEF may be a potential biomarker in ALI. To extend and translate that finding, we have performed the molecular cloning and characterization of canine PBEF cDNA in this study. Deduced amino acid sequence alignment revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 21 publications
2
54
2
Order By: Relevance
“…Leptin, an adipokine that is considerably smaller than visfatin (16 vs. 52 kDa; 167 vs. 473 amino acids), crosses the blood-brain barrier (BBB) via an active, saturable transport system (17) and displays a 5-to 10-fold less pronounced CSF-to-plasma ratio than that observed for visfatin in the present experiments (18). This pattern suggests that circulating visfatin can likewise enter the brain compartment, probably also via an active transport mechanism, although it cannot be ruled out that there are central nervous secretion sites for the peptide (19). In our study, CSF visfatin levels decreased with increasing plasma visfatin levels and adiposity, supporting the assumption that visfatin transport across the BBB is impaired when circulating visfatin increases as a result of excess body fat.…”
Section: Discussioncontrasting
confidence: 68%
“…Leptin, an adipokine that is considerably smaller than visfatin (16 vs. 52 kDa; 167 vs. 473 amino acids), crosses the blood-brain barrier (BBB) via an active, saturable transport system (17) and displays a 5-to 10-fold less pronounced CSF-to-plasma ratio than that observed for visfatin in the present experiments (18). This pattern suggests that circulating visfatin can likewise enter the brain compartment, probably also via an active transport mechanism, although it cannot be ruled out that there are central nervous secretion sites for the peptide (19). In our study, CSF visfatin levels decreased with increasing plasma visfatin levels and adiposity, supporting the assumption that visfatin transport across the BBB is impaired when circulating visfatin increases as a result of excess body fat.…”
Section: Discussioncontrasting
confidence: 68%
“…Although the exact role of visfatin continues to be elucidated, a critical role in pathobiology is suggested by its high degree of conservation throughout evolution (4,11,12,16). Accumulating evidence suggests that visfatin exerts important dual effects as an intracellular cell cycle regulatory protein (iNampt), in addition to secreted cytokine (eNampt), capable of modulating innate immunity and inflammatory responses across various cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicated that visfatin is an adipokine with insulin-like function and this effect varies depending on the amount of insulin., It has been reported that hyperglycemia causes increasing visfatin levels (42). In this regard, Haider et al (5) demonstrated that insulin injection in diabetic patients prevents increasing plasma visfatin, therefore, reduced insulin occurred after pancreatic beta cells dysfunction occurred which may be compensated for changes in visfatin concentration (43).…”
Section: Discussionmentioning
confidence: 99%